Plant selection for green infrastructure: a review of recommended species for stormwater management devices - Fernanda Nóbrega dos Santos, Maria; Enokibara, Marta; Solange Gurgel de Castro Fontes, Maria (Revista Nacional de Gerenciamento de Cidades, 2022)
Currently, one of the research gaps in the development of green infrastructure (GI) landscape projects, lies in plant selection, which are adequate to the GI existing devices and to regional characteristics. Therefore, the objective of this work was to perform a systematic literature review of GI in Brazil, focusing on stormwater management devices and their recommended species. A search was performed on Google Scholar, which identified 196 articles published in national journals by the end of 2019, which simultaneously contained the words ‘espécie’ (‘species’) and ‘infraestrutura verde’ (‘green infrastructure’) – and spelling variations in Portuguese. However, as GI is a wider concept and can encompass several strategies, the articles underwent an exploratory reading to verify which ones were directly related to the research objective. Seven articles fell within the scope, and 82 plant species were identified as recommended for use in the projects, some species with extensive documented experience on water treatment devices, while others only a suggestion for future use. In addition, complementary information about the species was surveyed to enable its use in landscape projects, such as: indication of use; botanical family; plant growth forms; substrate; origin; endemism; and distribution in the Brazilian Phytogeographic Domains (Amazonia, Caatinga, Cerrado, Mata Atlântica, Pampa, and Pantanal). This material was organized in a database, which can serve as a subsidy for the consolidation of a plant repertoire to be used in landscape projects with this purpose in Brazil.